Dampak wabah covid-19 terhadap pendapatan pelaku usaha wisata pantai meleura Desa Lakarinta Kecamatan Lohia Kabupaten Muna - Safiah, Asmaul; Yusuf, Sarini; Mansyur, Akhmad; Piliana, Wa Ode; Risfandi (Jurnal Sosial Ekonomi Perikanan, 2022)
The Covid-19 pandemic is suspected to have affected the income of business actors in the tourism sector. This study aims to determine the amount of income earned by business actors before and during the Covid-19 outbreak in Meleura Beach Tourism, Lakarinta Village, Lohia District, Muna Regency, Southeast Sulawesi. This study used a random sampling method based on area and a systematic random sample with a total of 30 respondents consisted of 1 respondent from government elements in this case the Head of Lakarinta Village and 29 respondents from the community. The data collection techniques used are by observation methods, interviews, literature studies, and documentation. The data is analyzed using the revenue analysis formula. The results showed that the income of business actors in Meleura Beach tourism has changed. The monthly income before the Covid-19 outbreak was IDR. 7,286,400 for the Government and IDR. 10,889,372 for the community. Meanwhile during Covid-19, the monthly income of business actors decreased to IDR. 1,618,800 for the government and IDR. 3,336,528 for the community. A significant decrease in income has been experienced by business actors and the government at the Meleura Beach tourist site, therefore they need to be incentivized by the local and central governments.